Twenty-First Century Skills and Their Relationship to The Quality of Psychological Life Among a Sample of Students at King Abdulaziz University in Jeddah (The International Journal for Scientific Research, 2023)
Accordingly, the current study aimed to identify the relationship between twenty-first century skills and psychological quality of life among female students at King Abdulaziz University in Jeddah. To achieve its purpose; It relied on the descriptive correlational approach, as the study was applied to a sample of (214) undergraduate students at King Abdulaziz University, and the measures of the twenty-first century skills and the quality of psychological life were prepared by the researcher, after verifying their psychometric characteristics, which came to a high degree. The study found the following results: There is a positive correlation, statistically significant, between the skills of the twenty-first century and the quality of psychological life among a sample of female students at King Abdulaziz University. The results concluded that the level of all twenty-first century skills (learning and creativity skills - digital culture skills - life and work skills) is available to female students at King Abdulaziz University at an advanced or high level. In addition, there were no statistically significant differences in the degrees of twenty-first century skills among a sample of female students at King Abdul Aziz University, due to the effect of the specialization variable. There are also statistically significant differences in the scores of twenty-first century skills among a sample of female students at King Abdulaziz University due to the impact of the current general assessment variable, in favor of female students whose assessment is high. Also, there are no statistically significant differences in the degrees of the quality of psychological life among a sample of female students at King Abdulaziz University due to the effect of the variable of specialization. Finally, there are statistically significant differences in the degrees of psychological quality of life among a sample of female students at King Abdulaziz University, due to the effect of the current general assessment variable.
Keywords: Twenty-First Century Skills; Psychological Well-being; Quality of Psychological Life; University Student